2020
DOI: 10.1088/1674-1056/ab928a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the properties of liquid film breakup induced by shock waves*

Abstract: We experimentally observed properties of liquid film breakup for shock-wave-initiated disturbances in air at normal temperature and pressure. The tested liquids include water and various glycerol mixtures. High speed camera and multiple-spark high speed camera were utilized to record the process of liquid film breakup. A phase Doppler particle analyzer was also used to record droplet size and velocity. The experimental results show that liquid viscosity plays a vital role in the deformation, breakup and atomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is because during the interaction between the shock wave and the water barrier, part of the energy of the shock wave is absorbed by the water barrier, and part of it forms a reflected wave that moves backward. No transmitted shock wave is formed behind the water barrier, so there is no step-up curve; the water barrier will form an aerosol cloud driven by the airflow behind the shock wave [10], and the pressure curves of measuring points p3 and p4 are the dynamic pressure curves of the aerosol cloud formed by the water barrier driven by the high-speed airflow after the shock wave. Comparing working conditions 1, 3, and 5 with experimental conditions 2, 4, and 6, it can be found that when the incident shock wave is Mach 1.6 and the water barrier thickness is 2 mm, the pressure peak when there is a water barrier seriously lags behind the overpressure peak under the condition of no water barrier.…”
Section: Experimental Devicementioning
confidence: 99%
“…This is because during the interaction between the shock wave and the water barrier, part of the energy of the shock wave is absorbed by the water barrier, and part of it forms a reflected wave that moves backward. No transmitted shock wave is formed behind the water barrier, so there is no step-up curve; the water barrier will form an aerosol cloud driven by the airflow behind the shock wave [10], and the pressure curves of measuring points p3 and p4 are the dynamic pressure curves of the aerosol cloud formed by the water barrier driven by the high-speed airflow after the shock wave. Comparing working conditions 1, 3, and 5 with experimental conditions 2, 4, and 6, it can be found that when the incident shock wave is Mach 1.6 and the water barrier thickness is 2 mm, the pressure peak when there is a water barrier seriously lags behind the overpressure peak under the condition of no water barrier.…”
Section: Experimental Devicementioning
confidence: 99%
“…Plates and shells are the most widely used tools in industrial and manufacturing applications. With the advancement of technology, applications of these devices in various fields, especially in micro and nano scales of such as micro/nano-electromechanical systems, [1][2][3][4][5] nano-mechanical and biological sensors, [6,7] fluidic transfer devices in medical laboratories, [8,9] are indisputable. Therefore, the studies of mechanical behaviors such as bending, [10] buckling, [11] vibration, [12] and wave propagation, [13] have been highly regarded by researchers in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…[30] The instability of Richtmyer-Meshkov is a key factor in the rupture and atomization of liquid films caused by shock waves. [31] Recently, stability analysis has become a hot and promising research topic. [32] It can provide some suggestions not only for the control of rumor propagation or virus transmission, but also for the clinical treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%